Boron: nothing boring about this intriguing element - Pereira, Greice Leal (2019)
Although Boron (B) is an essential micronutrient for plant growth and development, both deficiency and toxicity of B are important problems that severely affect agricultural production. This fact aside, the impact of these stresses in plants are still poorly understood. Thus, plants may respond differently to B availability through local and systemic signaling, whose mechanisms are yet poorly understood. Previous studies further suggest that ethylene plays a key role in the responses induced by B deficiency in the root system. The main goal of this work was to better understand the physiological and metabolic mechanisms underlying stress caused by B deficiency and excess, as well as to better understand the connections between ethylene and B in modulating plant growth. For this purpose, the responses of different conditions of B availability (deficiency, adequate and toxicity) were investigated in Arabidopsis and ethylene mutant tomato (Solanum lycopersicum) plants. The results obtained in this work demonstrate physiological and metabolic alterations in response to the contrasting conditions of B and that these responses are likely able to generate energy and maintain normal growth in B deficiency. It was also observed an association between B and ethylene levels mediating physiological and metabolic changes. Finally, our study sheds light on the complex relationship between B and ethylene and their overall effects on plant growth and development. The results described here helps to understand the plant's response mechanism to B deficiency and excess, and paves way for identifying the signaling pathways and genes involved in homeostasis and B accumulation in tissues. Although the absence of alterations in plant growth coupled with changes in fruit yield and seed production observed in response to change in the levels of ethylene is somewhat surprising it is tempting to speculate that pathways of energy metabolism and hormone metabolism are most likely highly interconnected at the whole plant level in a manner that allows the plant to prioritize reproductive organs during senescence under B stressfully conditions. It will be important to establish the functional significance of this observation in future studies in order to fully understand the molecular regulatory hierarchy regulating ethylene balance at the whole-plant level, particularly in response to fluctuations in B levels. Key-words: B deficiency, B toxicity, Ethylene, Central Metabolism.